PENGARUH WEBSITE DAN KESADARAN MEREK TERHADAP KEPUTUSAN PEMBELIAN PRODUK - THERESIA PRADIANI; DIESKA DAMARA (Pusat Publikasi dan Penerbitan Karya Ilmiah STIE Indonesia Malang, 2019)
This research is to find out the influence of website and brand awareness on purchasing decisions for products sold at www.MatahariMall.com. Types of causal research. MatahariMall.com consumer population, the sample used by 100 respondents with purposive sampling technique sampling. The technique of multiple linear regression data analysis. The results show that the website has a significant effect on purchasing decisions, reflected in the complete information displayed. Brand awareness seen from brand recognition has a significant effect on purchasing decisions, this shows that the website and brand awareness have a positive and significant effect on purchasing decisions for products sold at MatahariMall.com, seen from consumers deciding to buy after going through the process of selecting product brands offered at www.MatahariMall.com.